Consumers’ experiences of back pain in rural Western Australia: Access to information and services, and self-management behaviours. - Briggs, Andrew; Slater, Helen; Bunzli, S.; Jordan, J.; Davies, S.; Smith, Anne; Quintner, J. (BioMed Central, 2012)
Background: Coordinated, interdisciplinary services, supported by self-management underpin effective management for chronic low back pain (CLBP). However, a combination of system, provider and consumer-based barriers exist which limit the implementation of such models into practice, particularly in rural areas where unique access issues exist. In order to improve health service delivery for consumers with CLBP, policymakers and service providers require a more in depth understanding of these issues. The objective of this qualitative study was to explore barriers experienced by consumers in rural settings in Western Australia (WA) to accessing information and services and implementing effective self-management behaviours for CLBP. Methods: Fourteen consumers with a history of CLBP from three rural sites in WA participated. Maximum variation sampling was employed to ensure a range of experiences were captured. An interviewer, blinded to quantitative pain history data, conducted semi-structured telephone interviews using a standardised schedule to explore individuals’ access to information and services for CLBP, and self-management behaviours. Interviews were digitally recorded and transcribed verbatim. Inductive analysis techniques were used to derive and refine key themes. Results: Five key themes were identified that affected individuals’ experiences of managing CLBP in a rural setting, including: 1) poor access to information and services in rural settings; 2) inadequate knowledge and skills among local practitioners; 3) feelings of isolation and frustration; 4) psychological burden associated with CLBP; and 5) competing lifestyle demands hindering effective self-management for CLBP.Conclusions: Consumers in rural WA experienced difficulties in knowing where to access relevant information for CLBP and expressed frustration with the lack of service delivery options to access interdisciplinary and specialist services for CLBP. Competing lifestyle demands such as work and family commitments were cited as key barriers to adopting regular self-management practices. Consumer expectations for improved health service coordination and a workforce skilled in pain management are relevant to future service planning, particularly in the contexts of workforce capacity, community health services, and enablers to effective service delivery in primary care.